Religious muralism as a cultural stream of Puerto Rican identity: Visual voice against oppression - Cardalda, Elsa B.; Rodríguez, José R. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The present study attempts to show and to begin to understand, the motives of contemporary muralism, in terms of its historicity and primary narrative content. Within this purpose, we identified a wide range of murals (n=250), of which we selected those (n=49) of religious themes. We identified murals authored by or related to Puerto Ricans in communities with high concentrations of migrant Puerto Ricans in New York City. We used a qualitative method, recognizing distinctive symbolic elements in the murals that had psycho-social religious meanings.